Nazwy śmierci i okoliczności zgonu w wypowiedziach prasowych od XVII do początków XIX wieku - Pietrzak, Magdalena (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2024)
The subject of analysis is the names of death and circumstances of death extracted from the press from the 17th to the 19th century (from statements that can be classified into the common category of death notifications). Both vocabulary (including word compounds) directly naming the phenomenon of death and dying and substitute terms not directly referring to such experiences, were collected. The purpose of the article is, on the one hand, to indicate general naming preferences (lexical diversity, direct naming vocabulary vs. substitute vocabulary) and, on the other hand, to determine the extent to which the connections to the lexis of interest are fixed. The analysis showed that the group of terms directly naming death is formed by lexemes and word compounds belonging to the basic lexical resource of Polish. From the beginning of press coverage of death, the circumstances of death are noted: the time and place of death, the cause, the circumstances of dying (including the preparation for one’s own passing).